THE EVALUATION OF THE PERFORMANCE BASED BUDGETING IN HEALTH, EDUCATION, AND PUBLIC WORKS AGENCIES OF POLEWALI MANDAR REGENCY, WEST SULAWESI PROVINCE - Muhammad Sukri Arief (Mega Aktiva, 2020)
New paradigm of modern society pushes financial reform of regencies. One form of the reform is the application of performance-based budgeting. The budget compilation process and target demonstrate regencies’ opportunities to develop vision and mission as well as to materialize society expectation and desire in accordance with the regencies potentials. However, the implementation of the budget faces uneasy challenges. The subjects of this paper consist of budgeting process included planning, implementation, performance   measurement   and evaluation, and reporting.   This paper also describes problems in budgeting process. The technique of collecting data were collected by observation, in depth interview and analyzed by using qualitative method that was developed based on descriptive paradigm to describe comprehensive meaning of Polewali Mandar Regency, budgeting process. This research shows that in general, the idealism of performance based budgeting is not yet achieved. There are many mistakes in budgeting process sequences included planning, implementation, performance measurement and evaluation, and reporting. The less comprehensive communication, integration computerized application system, rewards and punishment system, and work ethic became the causes of the problems.